Non-medical costs incurred by critically ill patients with dengue, sepsis and tetanus within a major referral hospital in Southern Vietnam: a cost of illness study - Hung,TM; Nguyen,TN; Le,MT; Nguyen,PH; Nguyen,TP; Luong,THT; Le,BC; Pham,BT; Tieu,TTK; Tran,TDT; Lam,MY; Yacoub,S; et al. (BMJ Public Health, 2025)
Introduction Improving the knowledge of the costs of critical care is vital for informing health policy. However, cost data remain limited, particularly for low- and middle-income countries. The aim of this cross-sectional study is to describe the direct/indirect non-medical costs incurred by critically ill tetanus, sepsis and dengue patients and their families during their hospitalisation, using data from a major referral hospital in Vietnam.Methods This study was conducted within the Hospital for Tropical Diseases in Ho Chi Minh City, a tertiary referral hospital specialising in infectious diseases serving Southern Vietnam. Patients who were admitted to the intensive care unit (ICU) and diagnosed with either tetanus, dengue or sepsis were enrolled between April and November 2022. In total, 94 patients (and their caregivers) were interviewed. Structured questionnaires were used to estimate the direct non-medical costs and indirect costs (costs related to productivity/time losses) incurred during their hospitalisation by the patients and their caregivers (ie, the patients’ perspective).Results Overall, the estimated median total direct/indirect non-medical costs of the sample varied between US$511 and US$814 per patient, depending on the approach used to value the indirect costs. These total costs were broadly similar among sepsis and tetanus cases, but lower for dengue cases. The estimated indirect costs were highly sensitive to the approach used to monetise productivity losses and the valuation of informal care.Conclusion This study demonstrates that patients admitted to the ICU with a severe infection of these diseases can incur notable direct/indirect non-medical costs. These results highlight the importance of further research in this area. These findings are particularly relevant in the context of universal health coverage targets, as even with 100% coverage of medical costs, many families are still likely to suffer financial hardship.